Systemic lupus erythematosus as the concomitant manifestation of angioimmunoblastic T-cell lymphoma. Issue 2 (4th March 2017) - Suzuki, Akitake; Shoji, Norikazu; Aoki, Naoko; Asazuma, Naoki; Machinami, Rikuo; Kojima, Masaru; Okai, Takahiro
Abstract : Herein we report a case of the simultaneous occurrence of angioimmunoblastic T-cell lymphoma (AITL) and systemic lupus erythematosus (SLE) in a 76-year-old woman. She presented with fever, night sweats, and general malaise. A laboratory examination revealed leukopenia, anemia, polyclonal hypergammaglobulinemia, hypocomplementemia, positive results for anti-nuclear antibodies and anti-double strand DNA (anti-dsDNA) antibodies, and mild proteinuria. A computed tomography scan of the abdominal cavity showed multiple swollen intra-abdominal and intra-pelvic lymph nodes. A biopsy specimen obtained from the peri-iliac lymph node confirmed the diagnosis of AITL, while renal biopsy results were consistent with lupus nephritis, International Society of Nephrology and Renal Pathology Society class V. These results indicated that our patient developed SLE concomitantly with AITL. These findings will lead to further understanding of the pathogenic mechanism of SLE.